Geometrical inequalities in acute triangle involving the medians V - Béla Finta (Scientific Bulletin of the ''Petru Maior" University of Tîrgu Mureș, 2014)
The purpose of this paper is to demonstrate a new open question that generalizes previous open questions formulated by researchers in the field of geometrical inequal- ities. In this sense we have proved that in every acute triangle ABC from a < b < c does not result a^-2n + m_a^-2n < b^-2n + m_b^-2n < c^-2n + m_c^-2n; where n 2 N For the demonstration we have deduced two theorems that allowed the formulation of the main conclusion.